The Influence Of Transformational Leadership And Self Efficacy On Employee Performance Through Employee Engagement: Study of Semarang City Bapenda Employees - Indah Suwarni; Suparjo Suparjo ; Nurchayati Nurchayati ; Gita Sugiyarti (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
This research aims to analyze the influence of transformational leadership and self-efficacy on employee performance both directly and through employee engagement in employees of the Semarang City Regional Revenue Agency. The population in this study was all employees of the Semarang City Bapenda, the sample size used was 114 respondents, with a sampling technique using proportionate random sampling. The data source used was primary data, with a questionnaire data collection method. The analysis techniques used are path analysis and Sobel test. The results of the research analysis showed that transformational leadership, self-efficacy and employee engagement had a positive and significant effect on employee performance. Transformational leadership and self-efficacy have a positive and significant effect on employee engagement. The results of the mediation test state that the employee engagement variable can mediate the influence of transformational leadership on employee performance and the influence of self-efficacy on employee performance.